Presentation and research methodology of documentary data of the institucional center Israelite Center of Nilópolis guarded by the Jewish Historical Archive - Raposo, Fernanda Capri (Em Perspectiva, 2017)
The purpose of this article is to present some theoretical and methodological notes on documentary research in the documentation that compose the Institutional Fund Centro Israelita de Nilópolis (FI0018), guarded by the Historical Jewish Historical Archive - AHJB.